Pathogenic invasive microbes Trichoderma pleuroticola transform bacterial and fungal community diversity in Auricularia cornea crop production system - Ye, Lei; Zhang, Bo; Zhang, Lingzi; Yang, Xuezhen; Tan, Wei; Zhang, Xiaoping; Li, Xiaolin (Frontiers in Microbiology, 2023)
Pathogenic invasion of Trichoderma pleuroticola profoundly altered microflora in the Auricularia cornea crop production system, impacting diversity and composition in both artificial bed-log and fruiting bodies. A more complex ecological network between the diseased and healthy bodies.Researchers still have poor knowledge about how the important agricultural relationship between the composition of the microbiome of the artificial bed-log and the fruiting bodies is infected by the pathogenic invasive microbes T. pleuroticola, but this knowledge is crucial if we want to use or improve it. Here, we investigated 8 groups (48 biological samples) across 5 growth stages of the A. cornea production system using metagenomic technology. Diseased and healthy fruiting bodies exhibited distinct microbial compositions, while core members in artificial bed-logs remained stable.Core microbiota analysis highlighted Pseudomonas and Pandoraea bacterial genera, as well as Sarocladium, Cephalotrichum, Aspergillus, and Mortierella fungal genera as biomarker species after the bodies were treated with the pathogenic invasive microbes T. pleuroticola. In diseased bodies, these core members upregulated pathways including polymyxin resistance, L-arginine degradation II, superpathway of L-arginine and L-ornithine degradation, glucose degradation (oxidative), glucose and glucose-1-phosphate degradation, promoting fruit spoilage. Our data confirm that T. pleuroticola plays an important role in the early stages of disease development in the A. cornea crop generation system. The exposed volatile core microbiome may play an important role in accelerating T. pleuroticola-induced decay of fruiting bodies.